Paying the price of sweetening your donation: evidence from a natural field experiment - Environment for Development (2010)
Using a natural field experiment in a recreational site, a public good almost fully dependent on voluntary donations, we explored the crowding-out effect of gift rewards. First, we investigated whether receiving a map in appreciation of a donation crowded out prosocial behavior and found no significant effect of giving the map. Second, we explored the effect of adding the map to a treatment designed to increase donations. Interestingly, when the gift was combined with our attempt to trigger reputational and self image motives, the probability of donating decreased significantly, compared to the social reference treatment alone.